DK guide to mammals - Morgan, Ben, 1968- (London : Dorling Kindersley Limited, 2003)
Photographs and text introduce children to the world of mammals, discussing their habitats, behavior, anatomy, intelligence, and more.
'A Dorling Kindersley book.'
Includes bibliographical references : pages 63 and index.
Keywords: Mammals -- Juvenile literature